Christian Faith in Rural Taiwan and Campus Gospel Work - Mei Loh, y. (University of jaffna, 2024)
The aboriginal peoples of Taiwan have been historically disadvantaged to the extent that in Taiwan’s gleaming and expanding modern cities, few aboriginal people can be found – a concerning situation. Consequently, an initiative has been launched by Fu Jen Catholic University, New Taipei City, as an outreach project to redress the balance. Hanxi Village is in Yilan county, an area where the indigenous Atayal tribes dwell, and most of them hold the Christion faith. During their previous period of discrimination, their language and culture were not valued by the government, and they even had to have Chinese names. Over time their human rights have been duly respected; with the government also providing many subsidies and incentives for their education. Taiwan is a country with a fairly stable and progressive democracy. Scientific and technological research and development also plays a very important role in the world and plays a considerable role in Taiwanese society. Therefore, digital development has also penetrated into the gospel work on campus. Evangelism on campus is a very important service. The Fellowship of Faith, Hope and Agape in Chung Yuan Christian University cooperates with the university’s curriculum to engage in campus evangelism work. Over the years this fellowship has led many students to become Christians, and these students have subsequently performed very well in the workplace. In this paper I would like to use two approaches to talk about the evangelistic work of Christianity on campus in democratic Taiwan, as used respectively by Fu Jen Catholic University and Chung Yuan Christian University.
Keywords: Atayal; Christian faith; Campus; Taiwan; Evangelistic work of christianity